Chronic fatigue syndrome and occupational status: a retrospective longitudinal study. (5th December 2021) - Stevelink, S A M; Mark, K M; Fear, N T; Hotopf, M; Chalder, T
Abstract: Background: Few studies into chronic fatigue syndrome (CFS) have emphasized work-related consequences, including return to work after illness. Aims: This paper explores socio-demographic, work and clinical characteristics that are associated with occupational status among patients who were assessed at baseline and a follow-up point. Methods: Longitudinal data were assessed from patients affected by CFS who attended an outpatient CFS treatment service between 2007 and 2014. Employment status at baseline and follow-up was available for 316 patients. Data were also included on gender, age, duration of CFS, fatigue severity, type and number of treatment sessions, coping strategies, functional impairment, common mental disorders and physical functioning. Results: Most patients were female (73%) and had been affected by CFS for longer than 2 years (66%). Patients were followed up for an average of 285 days and over this period 53% of patients who were working remained in employment. Of the patients who were not working at baseline, 9% had returned to work at follow-up. However, of those working at baseline, 6% were unable to continue to work at follow-up. Age, fatigue severity, functional impairment, cognitive and behavioural responses, and depressive symptoms impacted on a patients' work status at follow-up. Conclusions: The findings indicated that it is possible for people with CFS to remain in work or return to work, despite having had a disabling illness. Work-related outcomes should be targeted in all people of working age.